2006
DOI: 10.1177/0269881106059693
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in the treatment of acute manic or mixed episodes in patients with bipolar I disorder: a 3-week placebo-controlled study

Abstract: This study compares the efficacy, safety, and tolerability of a partial dopamine agonist, aripiprazole, with placebo in the treatment of patients with bipolar I disorder experiencing an acute manic or mixed episode. In total, 272 hospitalized patients were randomized to aripiprazole 30 mg/day or placebo in this 3-week, double-blind, placebo-controlled trial. Dosing could be reduced to 15 mg/day for tolerability and, subsequently, increased to 30 mg/day based on clinical response. Primary efficacy measure was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(183 citation statements)
references
References 29 publications
14
160
1
7
Order By: Relevance
“…Aripiprazole was generally well tolerated over the entire 12-week study, with an adverse event profile similar to that seen in previous short-term 6,7 and long-term studies. 8,9 The incidence of adverse events related to extrapyramidal symptoms with haloperidol was more than double that with aripiprazole, as was the use of concomitant medications for the potential treatment of such symptoms.…”
Section: Tolerabilitysupporting
confidence: 69%
See 1 more Smart Citation
“…Aripiprazole was generally well tolerated over the entire 12-week study, with an adverse event profile similar to that seen in previous short-term 6,7 and long-term studies. 8,9 The incidence of adverse events related to extrapyramidal symptoms with haloperidol was more than double that with aripiprazole, as was the use of concomitant medications for the potential treatment of such symptoms.…”
Section: Tolerabilitysupporting
confidence: 69%
“…21,22 In previous studies, aripiprazole was started at 30 mg/day, 6,7 whereas this study demonstrated the efficacy of aripiprazole with a treatment regimen starting at 15 mg/day. As 42% of aripiprazoletreated patients were on 15 mg/day at week 3, this study demonstrated that a treatment regimen with a starting dose of 15 mg/ day can be an effective approach for treating patients with acute bipolar mania.…”
Section: Discussionmentioning
confidence: 54%
“…We did not perform further subgroup meta-analysis of trials with adults only as fewer than three datasets were available (Sachs et al, 2006;Young et al, 2009). We divided the trials into two categories by daily dosage (< 20 mg/day and > 20 mg/day) to evaluate whether or not there was a dose-dependent effect.…”
Section: Methodological Quality Of the Included Studiesmentioning
confidence: 99%
“…Therefore, 20 articles were eligible for the current meta-analysis (Carlson et al, 2012;El-Mallakh et al, 2012;El Mallakh et al, 2010;Findling et al, 2013;Findling et al, 2009;Findling et al, 2012;Jeong et al, 2012;Kanba et al, 2014;Keck et al, 2007;Keck et al, 2003;Keck et al, 2009;Muzina et al, 2008;Quante et al, 2010;Sachs et al, 2006;Thase et al, 2008;Tramontina et al, 2009;Vieta et al, 2005;Vieta et al, 2008;Woo et al, 2011;Young et al, 2009) (Table 1). …”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation